(untitled) (Research, Society and Development, 2021)
Introduction: Type 2 Diabetes Mellitus is a syndrome characterized by hyperglycemia, resulting from defects in insulin secretion, insulin action or both, in target tissues (liver, muscle and adipose tissue). This study aimed to verify the therapeutic effects of supplementation of yellow passion fruit peel flour (Passiflora Edulis f. flavicarpa Deg.) in the treatment of individuals affected by type 2 Diabetes Mellitus. Methodology: This is a narrative review, carried out through the selection and analysis of scientific articles and academic papers published between 2011 and 2021. Development: From the survey of studies, it was identified that yellow passion fruit peel flour has beneficial effects mainly in the control glycemic, due to the presence of soluble fibers, such as pectin, present in its bark, which increases the fiber content of the diet, thus reducing blood glucose and circulating lipids in the diabetic individual. Conclusion: The information provided by this study suggests the use of passion fruit peel flour as a complementary therapy to conventional treatments and can help health professionals to implement strategies that help diabetic patients make healthier food choices.